Charting back pain (Manchester, 2002)
" ... A new union report on back pain, which looked at a cross-section of its female membership, showed a high incidence of discomfort among workers involved in lifting, repetitive tasks, and poor working conditions or methods. The survey also casts doubt on the assumption that jobs previously described as ‘women’s work’ do not carry significant health risks. ..."